2013
DOI: 10.1080/07347332.2012.761317
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Reliability Analysis of Quality of Relationship Index in Cancer Patients

Abstract: Among psychosocial factors affecting emotional adjustment and quality of life, social support is one of the most important and widely studied in cancer patients, but little is known about the perception of support in specific significant relationships in patients with cancer. This study examined the psychometric properties of the Quality of Relationship Inventory (QRI) by evaluating its factor structure and its convergent and discriminant validity in a sample of cancer patients. A total of 388 patients complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
2
7
1
2
Order By: Relevance
“…The CFA results revealed that a three-factor model (Pierce et al, 1991) provided an adequate fit to the data. Other studies (Verhofstadt et al, 2006;Reiner et al, 2012& Cousson-Gélie et al, 2013 have also confirmed the three-factor structure proposed by Pierce et al (1991). Although, Nakano et al (2002) and Matos et al (2013a) found a two-factor structure.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The CFA results revealed that a three-factor model (Pierce et al, 1991) provided an adequate fit to the data. Other studies (Verhofstadt et al, 2006;Reiner et al, 2012& Cousson-Gélie et al, 2013 have also confirmed the three-factor structure proposed by Pierce et al (1991). Although, Nakano et al (2002) and Matos et al (2013a) found a two-factor structure.…”
Section: Discussionsupporting
confidence: 51%
“…The psychometric properties of the QRI have been studied and results indicated that the QRI has good validity (e.g., discriminant, predictive), and temporal stability (e.g., Cousson-Gélie, Chalvron, Zozaya & Lafaye, 2013;Nakano et al, 2002;Pierce, 1994;Pierce et al,1991;Verhofstadt, Buysse, Rosseel & Peene, 2006). Pierce et al (1991) investigated the factor structure of the QRI in a sample of undergraduates who completed the QRI for several close relationships (e.g., mother, father, and friend).…”
Section: Introductionmentioning
confidence: 98%
“…It should also be noted that this study did not meet the results obtained in other studies carried out previously, that found a tri-factorial structure that matches the original version: in Portuguese context, studies of Neves (2006), Marques et al (2014) and Marques et al (2015); and internationally, studies from Verhofstadt et al (2006), Reiner et al (2012) and Cousson-Gélie et al (2013).…”
Section: Eissn: 2357-1330 Selection and Peer-review Under Responsibilitcontrasting
confidence: 52%
“…Nakano et al (2002) found in a small sample of the Japanese population (40 couples), a factorial structure of 2 factors, where the depth and social support subscales were combined; Verhofstadt, Buysse, Rossel and Peene (2006) conducted a study with 286 Belgian couples and concluded that the original three-factor structure was the most suitable; Reiner, Beautel, Skaletz, Brahler and Stobel-Richter (2012), with a sample of 1494 adults, conducted the German validation of this scale, that also confirmed the tri-factorial structure of the QRI; Cousson-Gélie et al (2013) performed a confirmatory factor analysis, in France, with 388 cancer patients, which also corroborated the original factorial structure.…”
mentioning
confidence: 99%
“…Breast cancer survivors maintain satisfying marital relationships by promoting mental health and role adjustment through emotional support, which is a key marital concept. Social support is an important influential factor in PTG in BC survivors, for whom health‐ and adjustment‐related support should be provided by spouses, as they are the primary source of support . These results indicate that mutual support between spouses, as partners in growth and healing, could reduce the effects of external events, which highlights the need for couples counseling programs.…”
Section: Discussionmentioning
confidence: 99%